MANFAAT HASIL BELAJAR BUSANA PENGANTIN SEBAGAI KESIAPAN MEMBUKA BRIDAL BOUTIQUE - Miftahul Janah; Mally Maeliah (Universitas Pendidikan Indonesia, 2017)
Wedding Dress is a subject of boutique concentration in Studi Program of fashion design Education Faculty of the Technology and Vocational Education, Indonesia University of Education. The aim of this research of being to receive the data about the benefit of studying results of Wedding Dress in terms of western concepts, skills of making techniques western wedding dress, knowledge and skills to make decorative trimming on western wedding dress as readiness to open Bridal Boutique. The research method that used is descriptive method and collecting data using a form of a questionnaire. The sample of research used the purposive sampling, that is the student of boutique concentration in Studi Program of fashion design Education Faculty of the Technology and Vocational Education, the generation of 2011 and 2011 and has made a western wedding dress, that was total 34 people. The results showed in general more than half of respondents have felt the benefits of learning outcomes as the Bride Dress bridal boutique opened readiness. The conclusion from this study that students can take advantage from studying results of Wedding Dress as readiness to open Bridal Boutique.